Otitis Media and Its Association With Hearing Loss in Chinese Adults: A Population Based Study of 4 Provinces in China - Luo, Yanan; He, Ping; Wen, Xu; Gong, Rui; Hu, Xiangyang; Zheng, Xiaoying (Frontiers in Public Health, 2022)
Objective Otitis media is a recognized cause of significant hearing loss, particularly in developing countries. This study aimed to investigate the relationship between otitis media and hearing loss in Chinese adults aged 18 years and older. Methods The survey was based on WHO Ear and Hearing Disorders Survey Protocol and 36,783 adults at the ages between 18 years and above were selected in this study. Trained local examiners performed pure tone audiometry to screen people with hearing loss, and those who were screened positively for hearing loss were referred to audiologists to make final diagnosis. All participants underwent clinical ENT check-up and otoscopic examination by doctors trained in ENT. Each participant was assigned a single middle ear diagnosis. Diagnoses were assigned as per the WHO classification of ear and hearing disorders. Results Logistic regressions showed that higher prevalence of hearing loss was found in participants with otitis media, with an unadjusted odds ratio of 5.67 (95%CI: 4.66, 6.90). The next two models (Model 2-3) had slight impact on ORs. The interaction of residency and otitis media was statistically significant (OR=1.70, 95%CI=1.15, 2.53); otitis media patients in rural areas had higher risk of hearing loss. However, this interaction became not significant in 65 years old and above participants. Conclusions Otitis media was associated with the risk of hearing loss. Compared with urban patients with otitis media, rural patients have the higher risk of hearing loss. Action to reduce the risk of hearing loss in otitis media will require attention to rural-urban disparities.